2007
DOI: 10.1097/01.tp.0000259978.62139.9d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activin A on Pancreatic Ductal Cells in Streptozotocin-Induced Diabetic Rats

Abstract: The pancreatic ductal cells could be efficiently differentiated into insulin secreting cells by activin A treatment in vitro and normalize hyperglycemia in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The signals leading to upregulation of pancreatic β-cell performance during pregnancy are unknown. However, the action of activin A on pancreatic β-cells (14,15), our finding of low FSTL3 levels in the serum of women with GDM, and the previous reports of elevated activin A levels in pregnancies affected by GDM (16,17) underscore a possible role for activin A in the promotion of islet cell hyperplasia and increased insulin secretion during pregnancy.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The signals leading to upregulation of pancreatic β-cell performance during pregnancy are unknown. However, the action of activin A on pancreatic β-cells (14,15), our finding of low FSTL3 levels in the serum of women with GDM, and the previous reports of elevated activin A levels in pregnancies affected by GDM (16,17) underscore a possible role for activin A in the promotion of islet cell hyperplasia and increased insulin secretion during pregnancy.…”
Section: Discussionsupporting
confidence: 61%
“…Further evidence supporting a role for FSTL3 in glucose homeostasis includes the biological activities of activin A and myostatin, which are antagonized by FSTL3. Activin A promotes proliferation of β-cells and secretion of insulin (14,15); activin A levels were found to be elevated in pregnancies affected by GDM in previous studies (16,17). In mouse models, the absence of myostatin promotes insulin sensitivity and protects against weight gain (18,19).…”
mentioning
confidence: 94%
“…More recently, it was found that activin expression is increased in ductal tissues and co-localized with the cytokeratin maker for ductal cells after reduction of β-cell mass with streptozotocin or partial pancreatectomy (Zhang et al 2002). Activin was also found to increase proliferation of rat ductal cells in vitro , as well as to induce their differentiation into insulin producing cells expressing PDX-1, Ngn-3, and other genetic markers of β-cells (Park et al 2007). Glucose-stimulated insulin secretion was also enhanced in these cells, and when transplanted, were able to reverse streptozotocin-induced diabetes in rats (Park et al 2007).…”
Section: B Advances In Biological Actions Of Activin In Adults and Ementioning
confidence: 99%
“…Interestingly, this expression is upregulated in models of pancreatic regeneration after injury although the proliferative index of activin or activin receptor-positive cells was not elevated. Moreover, follistatin is expressed in expanding ductal epithelium and localized to proliferating cells, suggesting that inhibition of activin action by local follistatin might lead to increased proliferation during this particular stage [35,36]. Perhaps the increased activin expression and presumably action contributes to differentiation of ductal epithelium into endocrine cells that has been observed after injury [37].…”
Section: Activin/tgfβ Subfamily Signaling In Regulation Of β-Cell Andmentioning
confidence: 99%